1991
DOI: 10.1007/bf00048099
|View full text |Cite
|
Sign up to set email alerts
|

Flow reactor and triple quadrupole mass spectrometer investigations of negative ion reactions involving nitric acid: Implications for atmospheric HNO3 detection by chemical ionization mass spectrometry

Abstract: Atmospheric nitric acid measurements by ACIMS (Active Chemical Ionization Mass Spectrometry) are based on ion-molecule reactions of CO3(H20) . and NO~(H20), with HNO 3. We have studied these reactions in the laboratory using a flow tube apparatus with mass spectrometric detection of reactant and product ions. Both product ion distributions and rate coefficients were measured. All reactions were investigated in an N2-buffer (1-3 hPa) at room temperature. The reaction rate coefficients of OH-, O2, 03, CO4, CO3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…(Möhler and Arnold, 1991;Schneider et al, 1998). A recent study has reinvestigated this IMR and confirmed our rate coefficients (Guimbaud et al, 1998).…”
Section: Cims Apparatussupporting
confidence: 82%
“…(Möhler and Arnold, 1991;Schneider et al, 1998). A recent study has reinvestigated this IMR and confirmed our rate coefficients (Guimbaud et al, 1998).…”
Section: Cims Apparatussupporting
confidence: 82%
“…CO − 3 is also known to be formed in air by ion-molecule reactions involving CO 2 (Möhler & Arnold, 1991). In the present experiment, ultra-pure air supplied from a cylinder was used, but at least a few ppb of CO 2 is usually present.…”
Section: Mass Spectral Measurementsmentioning
confidence: 99%
“…CO 3 − forms clusters with H 2 O as well as with HNO 3 . The direct reactions with HNO 3 occur as well: (after Möhler and Arnold [1991]). Cl − forms clusters with H 2 O and HCl and reacts with HNO 3 to form NO 3 − .…”
Section: Model Descriptionmentioning
confidence: 99%